Influence of TNF and IL17 Gene Polymorphisms on the Spondyloarthritis Immunopathogenesis, Regardless of HLA-B27, in a Brazilian Population - Rocha Loures, Marco A. (Mediators Inflamm, 2018)
BACKGROUND AND OBJECTIVES: Spondyloarthritis (SpA) represents a heterogeneous group of immune-mediated inflammatory diseases that have overlapping clinical features, genetic predisposition, and pathogenic mechanisms. Hence, we investigated, through a case-control study, whether single-nucleotide polymorphisms of TNF and IL17 genes are associated with SpA, ankylosing spondylitis (AS), and psoriatic arthritis (PsA) in a mixed Brazilian population. METHODS: Genotyping of TNF-308 (rs1800629), TNF-238 (rs361525), IL17A (rs2275913), IL17F (rs763780), and HLA-B27 polymorphisms was performed in 243 patients with SpA and 210 controls from Southern Brazil using SSOP-Luminex (One Lambda) and PCR-SSP assays. RESULTS: Significant associations were confirmed between the HLA-B27 marker and SpA, AS, and PsA diseases. While TNF-308 (rs1800629) AA/GA, IL17A (rs2275913) AA/GA, and IL17F (rs763780) CC/TC genotype frequencies were associated, in the dominance inheritance model, with SpA and AS, regardless of gender, the presence of HLA-B27, TNF-238 (rs361525) GA/AA, IL17A (rs2275913) AA/GA, and IL17F (rs763780) genotypes was associated with PsA. CONCLUSION: In this Brazilian population, TNF and IL17 gene polymorphisms responsible for the expression of important inflammatory cytokines were associated with overall SpA, and, specifically, with AS and PsA, regardless of gender and HLA-B27. However, future larger studies with different ethnicities may be necessary to confirm these genetic associations.